How Factors of Personal Attitudes and Learning Environments Affect Gender Difference toward Mobile Distance Learning Acceptance - Liaw, Shu-Sheng; Huang, Hsiu-Mei (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
Mobile technology for learning empowers the shift from traditionally pure instructor-centered classroom teaching to fully learner-centered educational settings. Although mobile learning (m-learning) accessing Internet resources anytime and anywhere, the issue of the relationship between gender perspectives and m-learning environments has been a controversial topic. Therefore, the main research objective of the research is to explore gender differences toward APP-based m-learning environments. Subjects of the study were selected university students who had already used an APP-based m-learning system for one month. A total of one hundred fifty nine valid questionnaires were collected, spilt evenly between female and male students. The statistical analyses lead to significant conclusions. Both female and male learners have highly positive perceptions toward m-learning. Additionally, the proposed research model is an acceptable conceptual model for investigating female and male learners’ attitudes. Furthermore, factors of personal attitudes and learning environments affect gender difference toward m-learning acceptance.